Dule Urwed and Boxing: The Production of Dule Knowledge via Baby San Blas - Haglund, Sue (InTensions, 2014)
This article is about the production of Dule knowledge and how it is conveyed in Panama’s boxing world. The physical performance of boxing movements creates spaces for Dule presence and serves as a boundary marker for both Panamanian and Dule cultures. I will discuss and examine the participation of my grandfather Dule boxer Ricardo Walker, also known as Baby San Blas, who was successful in his boxing matches and how the conflicting stories of this Indigenous boxer in Panama’s sporting world was, and is, political. The layers of the boxing world exposed via his performance reveals a production of knowledge for participants and their practices while dismantling and reconstructing those spatial practices.